Моделювання форм розвитку зеленого туризму в Україні - Збарський, В. К.; Грибова, Діана Вікторівна; Грибова, Диана Викторовна; Hrybova, Diana (Видавничий дім «Гельветика», 2020)
UK : У статті проаналізовано напрями підвищення ефективності малих форм туристичної діяльності в сільській місцевості. Відзначено важливість туристичного бізнесу як фактору сприяння соціально-економічному розвитку регіонів. Обґрунтовано необхідність розроблення практичних рекомендацій щодо підвищення ефективності економічної діяльності малих форм туристичного бізнесу. Вказується на важливість зеленого туризму як складника національного туристичного бізнесу. Розроблено модель організації туристичної діяльності у формі зеленої садиби на базі селянського господарства. Проведено порівняльний аналіз ефективності функціонування селянського господарства у сфері зеленого туризму та інших видів діяльності. Доведено більшу привабливість зеленого туризму для селянського господарства як використання наявного ресурсного потенціалу. EN : The article analyzes the ways to increase the efficiency of small forms of tourism in rural areas. The importance of tourism business as a factor in promoting socio-economic development of regions is noted. The necessity of development of practical recommendations on increase of efficiency of economic activity of small forms of tourist business is substantiated. The importance of green tourism as a component of the national tourism business is pointed out. The model of the organization of tourist activity in the form of a green estate on the basis of a peasant economy is developed. The purpose of the project is the organization of maintenance of effective functioning of a green estate of a basic category as a basis for the further development. It is planned to use 0.3 hectares of land for this form of economic activity. It is also planned to involve the available material, technical and labor resources of a peasant family for the organization of this area of entrepreneurial activity. The main idea of the project is to implement on a regular basis a wide range of cultural and entertainment activities for client groups of 40 to 60 people. In particular, it is assumed that the amount of current costs in general will not change, only in the autumn-winter period will increase slightly utility bills. Alternative models of organization of economic activity of green estates are developed. The first option involves the presence of 1 working person who performs all production and economic, maintenance, accounting and management and other functions, receiving 20,000 hryvnias each month. In this case, the employee must have a wide range of professional competencies, which in some way negatively affects their practical implementation. The comparative analysis of efficiency of functioning of a peasant economy in the field of green tourism and other kinds of activity is carried out. The greater attractiveness of green tourism for the peasant economy as a use of available resource potential has been proved. It is noted that the proposed models should be considered as a starting project for the further development of this form of rural family business.
Modeling of forms of green tourism development Ukraine
Keywords: туристичний бізнес; зелений туризм; моделювання; соціальний ефект; tourism business; green tourism; modeling; social effect